Pelatihan Pembuatan Produk Teh Berbahan Dasar Jagung Sebagai Antioksidan Kepada Masyarakat - Nuralim Pasisingi; Miftahul Khair Kadim; Wila Rumina Nento (STMIK Royal, 2021)
Abstract: North Gorontalo has considerable potential, especially in the agricultural sector. One of the excellent agricultural sectors is the corn crop. Although corn is a popular commodity in North Gorontalo District, the utilization and diversification of its processed products is still low. Corn hair contains antioxidants, one of which can be developed into tea products. This activity aims to improve the skills of local communities in processing corn into antioxidant tea products. The community service activities were carried out in Bualo Village, Biau District, North Gorontalo for 45 days, starting from September 3 to October 18, 2020. The training was carried out by providing education about the use of corn as a basic ingredient for processing and continued with practical activities for making ready-to-brew antioxidant tea. The result of this training activity was an increase in the knowledge of the local community in Bualo Village about the use of corn as a basic material for processing antioxidant tea products along with attractive packaging. Keywords: antioxidant; bualo; tea Abstrak: Gorontalo Utara memiliki potensi yang cukup besar terutama pada sektor pertanian. Salah satu sektor pertanian yang menjadi primadona adalah tanaman jagung Meskipun jagung merupakan komoditi populer di kabupaten Gorontalo Utara, pemanfaatan dan diversifikasi produk olahnnya masih tergolong rendah. Rambut jagung mengandung antioksidan yang salah satunya dapat dikembangkan menjadi produk teh. Kegiatan ini bertujuan untuk meningkatkan keterampilan masyarakat lokal dalam mengolah jagung menjadi produk teh antioksidan. Kegiatan pengabdian dilaksanakan di desa Bualo, Kecamatan Biau, Gorontalo Utara selama 45 hari, mulai dari tanggal 3 September hingga 18 Oktober 2020. Pelatihan dilakukan dengan memberikan edukasi tentang pemanfaatan jagung sebagai bahan dasar pengolahan dan dilanjutkan dengan kegiatan praktik pembuatan teh antioksidan siap seduh. Masyarakat Desa Bualo telah memiliki keterampilan tambahan dalam membuat produk teh antioksidan dengan kemasan yang menarik sebagai produk inovasi dalam rangka meningkatkan perekonomian masyarakat lokal.Kata kunci: antioksidan; bualo; teh